2020
DOI: 10.48550/arxiv.2008.09526
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

BPS Maxwell-Chern-Simons vortices with internal structures: the Abelian Higgs and the gauged $CP(2)$ cases

J. Andrade,
Rodolfo Casana,
E. da Hora

Abstract: We investigate the existence of first-order vortices inherent to both the Maxwell-Chern-Simons-Higgs and the Maxwell-Chern-Simons-CP (2) models extended via the inclusion of an extra scalar sector which plays the role of a source field. For both cases, we focus our attention on the timeindependent configurations with radial symmetry which can be obtained through the implementation of the so-called Bogomol'nyi-Prasad-Sommerfield (BPS) prescription. In this sense, in order to solve the corresponding first-order … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Regarding the function A 0 , it has the very same expression displayed in Eq. (18), so E c = 4π|W (φ(r = 0))|. Considering the function in Eq.…”
Section: B Three Spatial Dimensionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding the function A 0 , it has the very same expression displayed in Eq. (18), so E c = 4π|W (φ(r = 0))|. Considering the function in Eq.…”
Section: B Three Spatial Dimensionsmentioning
confidence: 99%
“…The use of a field-dependent function coupled with the gauge field dynamical term has also been recently considered in [14] in the electric context, that is, in the presence of an electric charge fixed at the origin; there, we showed that the electric field has a behavior that cap-tures the basic feature of asymptotic freedom, an effect that is usually associated to quarks and gluons. It was also considered, for instance, in [15][16][17][18][19] to describe vortex configurations with internal structures in the plane in the magnetic context. Moreover, very recently, in [20] the authors studied the dielectric Skyrme model, that is, the Skyrme model where both the kinetic and Skyrme terms are multiplied by field-dependent functions, leading to new results of current interest.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation